Institutional Environment and Green Economic Growth in China - Xiaoxiao Zhou; Lu Wang; Juntao Du (Complexity)
As the answer to sustainability concerns, green economic growth has gradually attracted considerable attention. Notably, the optimization of the institutional environment contributes to green economic growth from the perspective of new institutional economics. However, few studies have systematically explained the connection between the institutional environment and green growth. In this study, the institutional environment was divided into three dimensions: governmental, legal, and cultural subenvironments. We adopted econometric models with the effect of every dimension on green growth and empirically analyzed with the generalized method of moments, based on Chinese provincial panel data from the years 2000–2016. The results indicated that there was an inverted U-shaped relationship between China’s institutional environment and its green growth. That is, the institutional environment can initially promote China’s green growth but, if it is not changed, will eventually inhibit it. In addition, the analysis on the three dimensions of the institutional environment highlighted that the role of the cultural subenvironment in green growth is greater than those of the governmental and legal subenvironments.